Research Summaries of the 1st Research Conference of the School of Agricultural Sciences of the National University, Costa Rica (ECA-UNA) - Peraza Badilla, Walter (2024)
The School of Agricultural Sciences (ECA) of the National University plays a crucial role in the generation, dissemination, and transfer of knowledge to society. Through its diverse programs, projects, laboratories, and academic activities, ECA addresses various strategic areas related to the management of agricultural resources, innovation in sustainable production systems, genetic improvement, and food security. As an academic unit, we are aware of the importance of disseminating and sharing the results of the main research conducted within the School. This is achieved by creating spaces to showcase the wide range of projects ECA undertakes to different stakeholders, including students, academics, producers, and the general public. The aim of these spaces is to foster multidisciplinary approaches that generate a positive impact in the search for solutions to the major challenges facing the agricultural sector, both nationally and regionally. In this context, the School of Agricultural Sciences organizes the 1st Research Conference as a key platform to present the main research conducted by this academic unit. This event seeks to share experiences with the entire university community and other stakeholders in the agricultural sector, fostering an enriching and collaborative dialogue. The realization of this event underscores the importance of joining efforts to promote innovation and sustainability in the agricultural sector, essential elements for the economic and social development of our country.